2022
DOI: 10.1155/2022/6121407
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect and Mechanism of Traditional Chinese Medicine on Myocardial Ischemia Reperfusion Injury

Abstract: After acute myocardial infarction, early restoration of myocardial perfusion by thrombolysis or percutaneous coronary intervention is the most effective way to reduce the size of myocardial infarction and improve clinical outcomes. However, recovery of blood flow to the ischemic myocardium may cause ischemia-reperfusion (I/R) injury, a phenomenon that instead reduces the efficacy of myocardial reperfusion. Traditional Chinese medicine (TCM) has long been used for the treatment of cardiovascular diseases and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Extract of Mollugo pentaphylla can effectively reduce the incidence of arrhythmia in rats, improve the activity of Ca 2+ -ATPase in myocardial tissue and maintain the levels at magnitudes comparable to those in sham-operated rats(Li et al. 2016 ), suggesting that Mollugo pentaphylla extract has a certain protective effect against Ca 2+ overload in MI/R injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extract of Mollugo pentaphylla can effectively reduce the incidence of arrhythmia in rats, improve the activity of Ca 2+ -ATPase in myocardial tissue and maintain the levels at magnitudes comparable to those in sham-operated rats(Li et al. 2016 ), suggesting that Mollugo pentaphylla extract has a certain protective effect against Ca 2+ overload in MI/R injury.…”
Section: Resultsmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) signalling pathway is an important pathway causing myocardial cell injury and apoptosis (Li et al. 2016 ). Two medicinal plants [ Diospyros kaki Thunb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, emerging attention has been made to handle diseases including cardiovascular disorders using substances identified from natural products. As a treasury for discovering functional compounds with disease treating potentials, Traditional Chinese Medicine (TCM) is elicting increasing interests and attempts to find natural substances from TCM that can attenuate myocardial injuries via different mechanisms has been made in the last decade (Liu et al, 2022). Puerarin (Pue) is an isoflavone extracted from the root of Pueraria lobate and a major functional component of the "Gegen soup" formula (Meng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that oxidative stress can be successfully induced by using hydrogen peroxide on cultured cells and in several animal models, particularly on the heart of amphibians [ 5 , 6 ]. An antioxidant can be defined as any substance capable, at a relatively low concentration, of competing with other oxidizable substrates and thus lowering or preventing the oxidation of these substrates [ 7 ]. Many studies have shown that plants have antioxidant properties largely due to their phenolic content [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%